4th IET International Conference on Power Electronics, Machines and Drives (PEMD 2008) 2008
DOI: 10.1049/cp:20080492
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a novel flux-switching permanent magnet integrated-starter-generator

Abstract: This paper presents a flux-switching permanent magnet machine for application of automotive integrated-startergenerator (ISG). Firstly, a typical three-phase flux-switching permanent magnet machine topology and its advantages are introduced. Secondly, optimal design of the machine to maximise torque capability is studied and final design data is given as the global optimisation for the target ISG. Finally, the performance simulation results are obtained and analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It can be found that the two machines share a common elaborate stator of twelve poles with embedded rectangular PMs and concentrated coils, with each possesses a robust and passive rotor of 10 and 14 poles respectively. The operation principle and general design guideline of such PMFS machines can be found in [2], while the detailed design and performance analysis of the proposed machine have been reported in [32]. The key design parameters of the PMFS machine, on which the torque ripple reduction and analysis in this study are based, are given in Table I. The PMFS machines, which inherently use unique doubly salient structure, still suffer from the inevitable torque ripple.…”
Section: Pmfs Machine and Torque Ripple Modelingmentioning
confidence: 99%
“…It can be found that the two machines share a common elaborate stator of twelve poles with embedded rectangular PMs and concentrated coils, with each possesses a robust and passive rotor of 10 and 14 poles respectively. The operation principle and general design guideline of such PMFS machines can be found in [2], while the detailed design and performance analysis of the proposed machine have been reported in [32]. The key design parameters of the PMFS machine, on which the torque ripple reduction and analysis in this study are based, are given in Table I. The PMFS machines, which inherently use unique doubly salient structure, still suffer from the inevitable torque ripple.…”
Section: Pmfs Machine and Torque Ripple Modelingmentioning
confidence: 99%
“…In recent years, numerous publications on FSPMs demonstrate a great tendency in both academia and industry towards their utilisation in different applications such as automotive industry [9][10][11][12], wind power [13][14][15][16], downhole pumps [17,18] and aerospace [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it also enables the stators of FSPM motors very suitable for modular production. In addition, owing to the fact that the flux due to magnets are magnetically in parallel with that from the armature windings, the magnets can withstand demagnetization which is required in flux-weakening operation [9], [10]. However, this may cause cooling problems since the PMs are surrounded by armature coils which contain the main heat source.…”
Section: Introductionmentioning
confidence: 99%